2016
DOI: 10.15359/ree.20-2.11
|View full text |Cite
|
Sign up to set email alerts
|

Diseño y evaluación de herramientas lúdicas de aprendizaje socio-ambiental para identificar actitudes, motivaciones y decisiones de la juventud rural campesina contemporánea

Abstract: The current and potential relationship of contemporary rural youth with the agricultural and natural patrimony (PAN, according to its Spanish initials) that they will inherit is little known, but vitally important. In this study, we designed, adapted, and evaluated a variety of socio-environmental learning tools in order to identify and reflect on the opinions, actions, and motivations of 14 to 17 year olds in an area of the Sepultura Biosphere Reserve in Chiapas, Mexico to use their PAN in the future. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For example, it can be observed that some topics are related to video games, two of them from a negative perspective [57,62], one about educational benefits [22], and finally a recent article about Classcraft [8], very related to MMORPGs [7,9]. Others are related to more physically interactive situations, like roleplaying [58,60,63] and LARPs [61] with applications for socialization, attitudes, and physical education, and several proposals including history [27,56], attitudes and values [30,55,60], mathematics [40], politics [59], sustainability [39], etc. Additionally, mainly in 2010, several articles had a more miscellaneous nature, with a more theoretical point of view: myths about RPGs [16], editorials and publications [52], profiles of RPG players [51], and definitions and concepts about RPGs [53].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it can be observed that some topics are related to video games, two of them from a negative perspective [57,62], one about educational benefits [22], and finally a recent article about Classcraft [8], very related to MMORPGs [7,9]. Others are related to more physically interactive situations, like roleplaying [58,60,63] and LARPs [61] with applications for socialization, attitudes, and physical education, and several proposals including history [27,56], attitudes and values [30,55,60], mathematics [40], politics [59], sustainability [39], etc. Additionally, mainly in 2010, several articles had a more miscellaneous nature, with a more theoretical point of view: myths about RPGs [16], editorials and publications [52], profiles of RPG players [51], and definitions and concepts about RPGs [53].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the citations belong to a 2010 Education in the Knowledge Society (EKS) monograph (128 citations). From a quantitative valuation, 19.05% of references [8,22,53,58] deal with video games and ICTs; 19.05% [58,60,61,63] with LARP/roleplays (differences between them are sometimes difficult to establish); 38.09% [18,27,30,39,40,55,56,59] about practical proposals and experiences in the classroom (without LARPs or ICTs) including history, gender, etc., and the rest deal with diverse issues, often more theoretical, with 23.81% [16,[51][52][53][54]]. This answer corresponds to MQ2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation